Role of Career Information Services towards Career Maturity Through Career Interests of Students - Sitoresmi, Duwi; Sugiyo, Sugiyo; Saraswati, Sinta (Jurnal Bimbingan Konseling, 2024)
Career maturity is essential as it enables students to select appropriate career paths and prepare for further studies. This study aims to identify the role effect of career information services on career maturity through students' career interests. A quantitative approach with an ex post facto correlation design was employed, involving 329 students from public vocational schools in East Semarang District. This research was conducted by involving regression analysis. The results of the regression analysis indicate that career information services affect students' career interests in public vocational schools in East Semarang District. Additionally, career information services impact students' career maturity in these schools. There is also an influence of career interest on career maturity among students in East Semarang District public vocational schools. Furthermore, career information services impact career maturity through students' career interests. The further implications of this study are discussed in the analysis section.